INNOVATIVE PLANT IDENTIFICATION: PLANT REFERENCES IN A NEW ACCESSIBLE FORMAT: VIRTUAL HERBARIUM FOR ECONOMIC PLANTS AND THEIR RELATIVES - Flaster, T. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Now that the FDA has passed the new GMPs it required manufacturers to qualify their starting materials and for the first time identify their plants “Plant identification has always been an area of weakness in the botanical industry”. Now new innovative tools that assure product quality and consumer satisfaction are needed. Now there is an online tool that meets our criteria, Herbarium Online (SM). Since 1995 Botanical Liaisons, LLC, has focused on the plant identification as a core service. With over 600 plants common in commerce, it is difficult for manufacturers, researchers and regulators to know what plants they have on their premises. Botanical Liaisons, has created HerbariumOnlineSM, a virtual herbarium for economic plants. With this innovative tool you can identify your starting materials by viewing ”zoomable” images of authenticated voucher specimens and their related TLC, microscopy and macroscopic samples. Multiple species of a genus are all online so a positive identification is possible. This presentation offers background information about the value of plant identification and a virtual walk through the virtual herbarium.